2017
DOI: 10.1016/j.energy.2017.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of renewable heating systems: An empirical test of the diffusion of innovation theory

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 80 publications
(96 reference statements)
1
37
0
1
Order By: Relevance
“…Previous studies using finite mixture of preference classes found that allowing for further heterogeneity within each preference class, by means of continuously varying random parameters, produced significant increases in model fit (Bujosa et al 2010, Greene and Hensher 2013, Campbell et al 2014, Boeri et al 2014, Farizo et al 2014, Yoo and Ready 2014, Franceschinis et al 2017. There is no a-priori strong rationale for negating this occurrence in our data.…”
Section: Gumbelmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies using finite mixture of preference classes found that allowing for further heterogeneity within each preference class, by means of continuously varying random parameters, produced significant increases in model fit (Bujosa et al 2010, Greene and Hensher 2013, Campbell et al 2014, Boeri et al 2014, Farizo et al 2014, Yoo and Ready 2014, Franceschinis et al 2017. There is no a-priori strong rationale for negating this occurrence in our data.…”
Section: Gumbelmentioning
confidence: 58%
“…To do so we specify choice probabilities using a latent class (LC) logit model, but a subset of taste coefficients, after testing, are also assumed to be continuosly random within preference classes. We name this a latent class random parameter logit model (LC-RPL) (amongst others Bujosa et al 2010, Franceschinis et al 2017 .…”
Section: Research Questions Theory and Methodsmentioning
confidence: 99%
“…Several studies analyse awareness [12,13] and estimate citizens' willingness to pay (WTP) for the use of renewable energy sources (e.g., [14][15][16][17][18][19][20]). A number of studies also investigate homeowners' preferences for renewable domestic heating systems using the discrete choice experiment (DCE) approach [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] or conjoint and variance analysis [36], and most of them suggest that whilst renewable energy adoption is notably valued by households, this value is not enough to counterbalance the importance of the economic factors while purchasing a new heating [24,25,27,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the existing studies of innovation resistance theory, innovation resistance drew little attention from researchers in the field of consumer behaviors, with only a few researchers [5][6][7][8][9] engaging in relevant studies. Most researchers focused on the discussions of innovation influences [10][11][12][13][14][15], innovation diffusion [16][17][18][19] and the characteristics and behaviors, as well as the relationship between these two, among early adopters [20,21]. Dedehayir et al [22] suggested that understanding the consumers' willingness and unwillingness to adopt innovations were equally important.…”
Section: Introductionmentioning
confidence: 99%